Expression of leucine-rich-repeat-kinase 2 (LRRK2) during embryonic development - Zechel, Sabrina; Meinhardt, Andreas; Unsicker, Klaus; Bohlen und Halbach, Oliver von (International journal of developmental neuroscience, 2010)
The LRRK2 gene was recently found to have multiple mutations that are causative for the most common inherited form of late onset Parkinson's disease. In the adult brain, LRRK2 mRNA is broadly expressed, also in regions other than the nigrostriatal system. In order to establish a basis for assessing more detailed functional implications of LRRK2 in development, we provide here an in-depth analysis of its mRNA expression patterns in neural and extra-neural tissues with a focus on murine embryonic development. LRRK2 mRNA is detectable at E8.5 in non-neural and at E10.5 in neural tissues. From E12.5 to E16.5, LRRK2 mRNA is prominently expressed throughout the neocortex and subsequently highly concentrated in ventricular and subventricular zones and cortical plate. In addition, developing cerebellar granule and Purkinje neurons and spinal cord neurons display robust LRRK2 expression. In non-neural tissues LRRK2 was highly expressed in limb interdigital zones, developing kidney glomeruli, and spermatogenetic cells. Together, our results suggest roles for LRRK2 in controlling proliferation, migration, and differentiation of neural cells as well as in morphogenesis of extra-neural tissues.